1981
DOI: 10.1099/0022-1317-53-1-169
|View full text |Cite
|
Sign up to set email alerts
|

Structural Polypeptides of Hazara Virus

Abstract: SUMMARYFour structural polypeptides of Hazara virus, an agent closely related to the Crimean-Congo haemorrhagic fever (C-CHF) viruses, were resolved by SDSpolyacrylamide gel electrophoresis. Three glycoproteins were identified (mol. wt. 84 000, 45 000 and 30 000) and were found to be associated with the virion envelope. A fourth polypeptide (mol. wt. 52000) was non-glycosylated and associated with the nucleocapsid. The structural proteins of Hazara virus differ markedly from those reported for other bunyavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…W e found the smallest of these proteins to be the nucleoprotcin, which is consistent with all prototypes of the four genera of the Bunyaviridae, where the smallest virion Hantaan virus proteins proteins are nucleocapsid-associated (Obijeski & Murphy, 1977). A study by Foulke et al (1981) has described two proteins, 42K and 30K, both smaller than the 45K nucleocapsid protein of Hazara virus as structural proteins. However, studies of viral proteins in cell extracts often demonstrate the presence of actin in the 42K range (Naito & Matsumoto, 1978); a 42K protein is evident in our Fig.…”
Section: Discussionsupporting
confidence: 52%
“…W e found the smallest of these proteins to be the nucleoprotcin, which is consistent with all prototypes of the four genera of the Bunyaviridae, where the smallest virion Hantaan virus proteins proteins are nucleocapsid-associated (Obijeski & Murphy, 1977). A study by Foulke et al (1981) has described two proteins, 42K and 30K, both smaller than the 45K nucleocapsid protein of Hazara virus as structural proteins. However, studies of viral proteins in cell extracts often demonstrate the presence of actin in the 42K range (Naito & Matsumoto, 1978); a 42K protein is evident in our Fig.…”
Section: Discussionsupporting
confidence: 52%
“…There in fact appears to be little variation in antigenic sites among CCHF viruses, which form a single antigenic group, by which they are distinguished from other nairoviruses, such as HAZV (Buckley, 1974;Foulke et al, 1981). More subtle antigenic difference within the CCHFV group have been defined using monoclonal antibodies (Ahmed et al, 2005), but it is unclear how such variation affects cross-protection among viruses in vertebrate hosts.…”
Section: Genetic Driftmentioning
confidence: 99%
“…Purified nairovirus virions contain three major structural polypeptides, a nucleoprotein (N, molecular weight 48 x I03 to 54 x 10 3) and two external glycoproteins (G1 and G2, molecular weights 72 x 103 to 84 x 103 and 30 x 103 to 40 x 103 respectively) . Foulke et al (1981) identified an additional glycoprotein of molecular weight 45 x 103 with purified virions of Hazara virus.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical analyses have shown the nairoviruses to have some characteristics in common with other members of the Bunyaviridae, but they nevertheless form a distinct group Foulke et al, 1981). As for other Bunyaviridae the nairovirus genome consists of three unique RNA segments demonstrated by oligonucleotide fingerprinting .…”
Section: Introductionmentioning
confidence: 99%